Chapter 1 Introduction Climate change and planned retreat - Ajibade, Idowu Jola (Taylor & Francis, 2022)
"This edited volume advances our understanding of climate relocation (or planned retreat), an emerging topic in the fields of climate adaptation and hazard risk, and provides a platform for alternative voices and views on the subject. As the effects of climate change become more severe and widespread, there is a growing conversation about when, where and how people will move. Climate relocation is a controversial adaptation strategy, yet the process can also offer opportunity and hope. This collection grapples with the environmental and social justice dimensions from multiple perspectives, with cases drawn from Africa, Asia, Australia, Oceania, South America, and North America. The contributions throughout present unique perspectives, including community organizations, adaptation practitioners, geographers, lawyers, and landscape architects, reflecting on the potential harms and opportunities of climate-induced relocation. Works of art, photos, and quotes from flood survivors are also included, placed between sections to remind the reader of the human element in the adaptation debate. Blending art - photography, poetry, sculpture - with practical reflections and scholarly analyses, this volume provides new insights on a debate that touches us all: how we will live in the future and where? Challenging readers' pre-conceptions about planned retreat by juxtaposing different disciplines, lenses and media, this book will be of great interest to students and scholars of climate change, environmental migration and displacement, and environmental justice and equity."